Measuring the financial liberalization index for Pakistan - Muhammad Idrees; Umar Hayat; Magdalena Rădulescu; Md Shabbir Alam; Abdul Rehman; Mirela Panait (Journal of Risk and Financial Management, 2022)
This paper aims to construct a bi-directional, financial liberalization index for Pakistan by considering various financial policy indicators (reforms). This study, by employing the principal component analysis method over a period of 1980-2018 (39 years), aims to determine the composite outcome in the case of developing a financial index. This study uses 14 financial policy indicators to investigate the degree of financial liberalization over a specified time period. The present study suggests a financial liberalization index for Pakistan considering the real-time change in the implementation process. The formulated index revealed that the recorded profitability of financial reforms was consistently high until 1998. Meanwhile, in the period from 1997 to 2003, the outcomes of financial reforms were surprisingly strong. Beyond 2004 and for the rest of the remaining years until 2018, the liberalization process recorded was comparatively slow. Thus, it was witnessed that all the key indicators, in the sense of regulation and liberalization, included determining the degree of financial liberalization. The consistency track of a liberalization index is a major focus of attention for policy makers, in order to capture the efficiency outcomes from various financial policy indicators, which were implemented beyond 2004. Furthermore, corporate risk in terms of better access to finance is also raised as a consequence of financial liberalization. Financial liberalization also resulted in a decrease in the cost of capital and improved the corporate governance.
Keywords: 330; financial liberalization index (FLI); Pakistan; principal component analysis (PCA)